Tiesiskā regulējuma ietekme uz ārvalstu tiešajām investīcijām Latvijas Republikā - Zlakomanovs, Andrejs (Latvijas Universitāte, 2012)
Diplomdarbs „Tiesiskā regulējuma ietekme uz ārvalstu tiešajām investīcijām Latvijas Republikā”. Autors - Andrejs Zlakomanovs. Darba mērķis ir analizēt investīciju līmeni kopš 2000. gada, īpaši uzsverot izmaiņas tajā pēc iestāšanas ES, kā arī apskatīt to tiesisko regulējumu valstī. Darba hipotēze ir (1) ka iestāšanās ES neizmainīja investīciju regulējumu un (2) ka investīciju tiesiskais regulējums neietekmē investīciju līmeni. Darbā ir pierādītas abas hipotēzes un papildus ir veikts Latvijas tautsaimniecības apskats. Pētījuma objekts ir ĀTI Latvijā. Darba priekšmets ir ĀTI tiesiskais regulējums Latvijā. Darbs ir izveidots trīs daļās. Pirmajā daļā tiek aprakstīts investīciju jēdziens, to loma ekonomikas attīstībā, analizēti investīcijas ekonomiskie aspekti un to saiste ar citiem ekonomikas attīstības elementiem. Otrajā daļā tiek definēti investīciju līgumu būtības, investīciju politikas juridiskie aspekti, apskatīti dažādi līgumi ar vairākām valstīm un to detaļas. Pēdējā daļā tiek apskatīta Latvijas tautsaimniecības un īpaši Latvijas investīciju attīstība no 2000. gada, kā arī tiek apstiprinātas hipotēzes, jo rezultātā ir secināts, kā pēc iestāšanas ES investīciju līmenis mainījās, neskatoties uz to, ka jaunu līgumu un likumu neieveda.

Diploma thesis "Law regulation impact on foreign direct investment in the Republic of Latvia". Author Andrejs Zlakomanovs. The objective is to analyze the level of investment since the year 2000, with particular emphasis on changes through the entry to the EU, as well as to take a look at the legal framework the country operates in. The hypothesis are (1) joining the EU did not change the investment law regulation framework and (2) that investment regulation do not affect the level of investment. The thesis has demonstrated support for both of the hypothesis and had also reviewed the development of the country in the last years. The object of research is the amount of FDI to Latvia. The subject of research is the law regulation of FDI in Latvia. The work is developed in three parts. In the first part the concept of investment, its role in economic development, economic aspects of investment analysis are presented and its connection to the whole eсonomic development is described. The second part defines the nature of investment contracts, legal aspects of the investment policy, concerns the various investment agreements with several countries. The last section analyses the Latvian economy and particularly the Latvian investment development, starting from the year 2000, as well as both hypotheses are confirmed, an as a result it has been concluded that after joining the EU the level of investment has changed, despite the fact that the new contract and the law regulations did not change. The objective is to analyze the level of investment since the year 2000, with particular emphasis on changes through the entry to the EU, as well as to take a look at the legal framework the country operates in. The hypothesis are (1) joining the EU did not change the investment law regulation framework and (2) that investment regulation do not affect the level of investment. The thesis has demonstrated support for both of the hypothesis and had also reviewed the development of the country in the last years. The object of research is the amount of FDI to Latvia. The subject of research is the law regulation of FDI in Latvia. The work is developed in three parts. In the first part the concept of investment, its role in economic development, economic aspects of investment analysis are presented and its connection to the whole eсonomic development is described. The second part defines the nature of investment contracts, legal aspects of the investment policy, concerns the various investment agreements with several countries. The last section analyses the Latvian economy and particularly the Latvian investment development, starting from the year 2000, as well as both hypotheses are confirmed, an as a result it has been concluded that after joining the EU the level of investment has changed, despite the fact that the new contract and the law regulations did not change.
Law regulation impact on foreign direct investment in the Republic of Latvia
Keywords: Ekonomika